“Watch and Wait” Strategy for Multicystic Dysplastic Kidney (MCDK): Status Survey of Perceptions, Attitudes, and Treatment Selection in Chinese Pediatric Urologists and Pediatric Surgeons - Wang, Qi; Shi, Zhengzhou; Jiang, Dapeng (Frontiers in Pediatrics, 2020)
To investigate the perceptions, attitudes, and treatment selection of Chinese pediatric surgeons regarding a "watch and wait" strategy for multicystic dysplastic kidney (MCDK). We used a cross-sectional survey in this study. We sent the questionnaire to pediatric surgeons to capture their views via the "Questionnaire Star" online survey platform between Nov and Dec 2019. The questionnaire contained the basic information and surgical experiences of the respondent, respondents’ awareness regarding the counseling of prenatally-diagnosed MCDK and the treatment of MCDK, and respondents’ knowledge regarding the imaging modalities, frequency, and duration of follow-up. Of the 200 questionnaires we sent, we received 151 responses. Of those 151 complete responses, most respondents were women (n=104, 68.9%), pediatric urologists (n=78, 51.6%), and practicing with at least 5 years of surgical experience (n=112, 74.2%); 11.9% reported > 20 years’ experience. Eighty-two surgeons (54.3%) provided positive counselling for prenatally-diagnosed MCDK. Ninety-nine surgeons (65.6%) advocated conservative management for MCDK, and only 14.8% of respondents suggested limiting the use of radiographic evaluation for MCDK. Surgeons working in academic teaching facilities and those from East China were more likely to select a “watch and wait” strategy. Chinese pediatric surgeons have inadequate knowledge of the “watch and wait” strategy for MCDK. An expert consensus on the strategy of “watch and wait” for MCDK in China is urgently needed to promote the application of this non-surgical treatment mode in clinical practice. A larger sample size is required to fully identify the current opinion of Chinese pediatric surgeons regarding the management of MCDK.